Evaluation of a next birth after caesarean antenatal clinic on women's birth intention and outcomes, knowledge, confidence, fear and perceptions of care - Martin, T.; Hauck, Yvonne; Fenwick, J.; Butt, Janice; Wood, Jennifer (Ten Alps Publishing, 2014)
Aim: In 2008, a Western Australian maternity hospital began a next birth after caesarean (NBAC) service to improve the quality of care offered to pregnant women who had experienced a caesarean section (CS) in a previous pregnancy. The aim of this study was to evaluate the NBAC service at three time points (booking visit, 36 weeks’ gestation and six weeks postnatal) to determine changes in childbirth fear, confidence, knowledge and intention to pursue a vaginal birth after caesarean (VBAC) in a current pregnancy, compared to those women receiving standard antenatal care. Method: A comparative descriptive study design was implemented following receipt of ethical approval from the study hospital. A total of 47 women who attended the NBAC service for their antenatal care and a comparison group of 45 women who attended the main hospital clinic were recruited. Descriptive statistics, chi-square and t-test analyses were used. Women provided additional qualitative comments at 36 weeks and six weeks postnatal regarding their perceptions of care, which were analysed using content analysis.Results: At recruitment, the comparison and NBAC groups were comparable for demographic variables and birth intention. Birth outcomes were not different with 15 out of 25 comparison women (60%) achieving their desired VBAC, compared to 20 out of 34 NBAC women (58.8%). At 36 weeks’ gestation, NBAC women had increased knowledge of behavioural techniques to assist with labour and birth (p=0.0004) and higher self-efficacy (confidence) scores (p=0.011). There were no differences in terms of childbirth fear with both groups reporting high mean childbirth fear scores. Content analysis highlighted the positive and negative aspects of women’s antenatal care experiences. Implications: Findings suggest that providing pregnant women who had experienced a previous CS with evidence-based information about birth options did increase their knowledge, confidence and satisfaction with care. Childbirth fear levels were high for both groups and midwives with appropriate skills may be ideally placed to provide counselling intervention in conjunction with antenatal care.